2011
DOI: 10.1007/s10753-011-9300-1
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Hyperoxia-induced Lung Injury in Rats by Adrenomedullin

Abstract: Oxidative stress and inflammation are involved in the pathogenesis of acute lung injury (ALI). Adrenomedullin (AM) is an endogenous peptide with anti-inflammatory and antioxidant properties. This study investigated that whether AM treatment may ameliorate hyperoxia-induced ALI in rats via inhibition of oxidative stress and inflammation. Rats were randomized to receive continuous intravenous infusion of AM or saline through a microosmotic pump, and then ALI was induced by exposing the animals in sealed cages >9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…4,17 IL-6 is known as an important inflammatory indicator. 4,23 Increased levels of IL-6 have been consistently shown to correlate with aggravated lung injury. 4,22 IL-6 deletion using an IL-6Yspecific inactivating antibody or IL-6 geneYdeficient mice results in ameliorated lung injury following ischemic acute kidney injury or bilateral nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,17 IL-6 is known as an important inflammatory indicator. 4,23 Increased levels of IL-6 have been consistently shown to correlate with aggravated lung injury. 4,22 IL-6 deletion using an IL-6Yspecific inactivating antibody or IL-6 geneYdeficient mice results in ameliorated lung injury following ischemic acute kidney injury or bilateral nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…3 A growing body of evidence suggests that suppression of the NF-JB pathway by non-specific NF-JB inhibitors can dampen lung injury. 3,4 NF-JB sequestered in cytoplasm in an unstimulated state through interaction with its inhibitory proteins, Inhibitory JB (IJB). Phosphorylation of IJB results in its ubiquitination and degradation, while NF-JB is activated and translocated from the cytoplasm to the nucleus.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that ADM administration or gene delivery attenuates hypertension, cardiac remodeling, and renal injury in various animal models (3,9,41,42,44,54,62,63). In the lung, adrenomedullin attenuates acute lung injury in animal models (24,37,57), attenuates pulmonary hypertension in animal models and in humans (34,38,39), and regulates allergen-induced airway hyperresponsiveness in mice (67). However, regulation of myofibroblast function and pulmonary fibrosis by ADM signaling has been poorly investigated, and this is the focus of this study.…”
mentioning
confidence: 99%
“…Neonatal rodents are recognized to be tolerant to high levels of hyperoxia compared to adults. Recently, hyperoxia-induced pulmonary molecular changes in the neonatal rat BPD model have been described; murine alveolar development begins on P4d and saccular division is completed by P14d (13). During the 2-week period of hyperoxia in this study, the survival rate of the hyperoxiaexposed rats was reduced to 73%, and the lung weight was reduced to a lesser extent than the body weight.…”
Section: Discussionmentioning
confidence: 49%
“…Under deep pentobarbital anesthesia (50 mg/kg, intraperitoneal), a midline incision was made through the sternum and abdomen, and whole-lung tissue was obtained. Lung and body weights were recorded at the time of sacrifice (12)(13)(14).…”
Section: Animalmentioning
confidence: 99%